THE KIAI AS A COMMUNITY RELATIONS AGENT IN SUSTAINING THE EXISTENCE OF ISLAMIC BOARDING SCHOOLS: A CASE STUDY AT PONDOK PESANTREN BURHANUL ABRAR BESUKI, SITUBONDO - Rifa’i, Moh.; Sholahuddin, Sholahuddin (Jurnal Al-Ijtimaiyyah, 2026)
This study examines the role of the kiai (Islamic boarding school leader) as an agent of community relations (hubungan masyarakat) in sustaining the institutional existence of Pondok Pesantren Burhanul Abrar, Besuki, Situbondo, East Java, Indonesia. Situated within the framework of Islamic community development and institutional communication, the study analyzes the strategies, patterns, and social dynamics through which the kiai builds and maintains relationships with surrounding communities, alumni networks, government actors, and the broader public. A qualitative research design with a case study approach was employed. Data were collected through in-depth interviews with pesantren administrators, student guardians (wali santri), alumni, and community figures selected through purposive sampling, complemented by participatory observation of da'wah activities, social services, and community interactions, as well as institutional documentation. Data analysis followed the interactive model of Miles, Huberman, and Saldaña comprising data condensation, data display, and conclusion drawing, with validity ensured through source, method, and time triangulation. The findings reveal that the kiai occupies a strategically central position in the pesantren's community relations system, functioning simultaneously as a charismatic leader, moral communicator, social capital builder, and cultural da'wah actor. The kiai's community relations strategies encompass personal communication, cultural engagement through local Islamic traditions, moral exemplarity, external da'wah activities across multiple regions, and alumni network strengthening through the IKSABA organization. These strategies have yielded measurable outcomes, including a growth in student enrollment from 220 santri in 2023 to 255 in 2024 and 290 in 2025, reflecting increasing public trust and the deepening social legitimacy of the institution. The study concludes that the kiai's role as a cultural public relations agent is the most dominant factor in sustaining the pesantren's existence, and contributes a replicable model of community-based Islamic institutional communication applicable to other pesantren in contemporary Indonesia.